General features, management strategies, and outcomes of symptomatic spontaneous isolated celiac artery dissection - Zhou, Fushuo; Zheng, Zhi; Pan, Youmin (Frontiers in Surgery, 2022)
Objectives: Spontaneous isolated celiac artery dissection (SICAD) is a rare condition that has not been fully investigated and reported, and very little is known regarding its prognosis and management. Here, we aimed to provide more evidence on the management strategy and outcome for symptomatic SICAD based on the experience of a single center. Methods: From January 2018 to December 2021, a total of consecutive 51 patients with symptomatic SICAD were retrospectively included in this study. These patients had been selectively treated with conservative treatment (n=31) or endovascular treatment (n=20). Baseline data, imaging findings, treatment strategy, outcomes, and follow-up data have been described and analyzed. Results: The mean age of the patients was 53.2±9.6 years, 44 (86.3%) were male, and 36 (70.6%) had hypertension. The median length of stay was 10.0 days. The complete remission rate was 92.2% on discharge. The median follow-up time was 21.0 months. A secondary intervention was required for two patients during follow-up in the conservative group, wherein one underwent a stent placement three months after discharge because of progression of symptoms and extension of dissection, and the other required intervention one month after discharge because of symptomatic progression. No secondary intervention was required in the endovascular group. Occasional and mild relapse of symptoms occurred in two patients in both the conservative and endovascular groups, with no secondary intervention. The length of dissection (25.5±11.8 mm vs. 19.1±7.4 mm, P=0.022) and complete remodeling rate (85.7% vs. 15.4%, P<0.001) in the endovascular group were greater than that in the conservative group. Conclusion: Patients with symptomatic SICAD who were selectively treated with conservative treatment or endovascular treatment had satisfactory early and medium-term outcomes. Endovascular treatment showed significant advantages in the complete remodeling of the celiac artery and presented with a lower rate of secondary intervention. Moreover, it was found to be a safe and effective remedy for failed conservative treatment.